Blended Amendments: A Sustainable Approach for Managing Nutrient Deficiency in Rice Fields: 10.32526/ennrj/19/202100032 - Datta, Madhumita Ghosh (Environment and Natural Resources Journal, 2021)
The application of chemical fertilizer provides absorbable soluble macronutrients for increasing rice yield while reducing the availability of micronutrients and occasionally halting nitrogen mineralisation in the soil. To lessen some of these undesirable effects of chemical fertilization, an effort has been made to prepare blended soil organic amendments by mixing organic materials like rice straw, dried cow-dung and compost prepared from eco-friendly wastes from the kitchen, backyard garden and dried cow-dung mixed in the ratio 1:2:2. Such prepared amendments were applied in the rice field by growing three high-yielding rice cultivars Dikhow, Chandrama and Naveen, in three different rice cropping seasons, pre-monsoon (Ahu), monsoon (Sali) and summer (Boro) during 2015-2016 and 2016-2017 for studying soil properties, crop growth and yield. The key finding of the investigation was that the soil amended with chemical fertilizer showed improvement in soil moisture compared to unamended soil in all three rice fields. However, chemically fertilized soil exhibited lower amounts of available phosphorus, available potassium, diethylenetriaminepentaacetic acid (DTPA) extracted iron and copper in Ahu field, DTPA extracted iron, copper and zinc in Sali field and immobilizing nitrogen in Boro field than blended amendments. Overall, chemical fertilizer + rice straw displayed more available nitrogen and yield in Ahu field, whereas, chemical fertilizer + dried cow dung showed the highest amount of zinc and copper along with the highest yield in Sali rice field and chemical fertilizer+compost had better moisture and soil organic carbon amounts with an ideal acidic pH supporting maximum yield in Boro rice field.